VD_FINDINFO HC / 2024 / 433 vom 16. April 2024 - VD Tribunal cantonal (2024)
BAIL À LOYER, ANNULABILITÉ, RÉSILIATION, PROLONGATION DU BAIL À LOYER, MOTIF | 257f al. 3 CO, 271 al. 1 CO, 271a al. 1 let. a CO, 272a CO